Systematic Literature Review of Market Efficiency in Emerging Markets - M, Yuliana; Maknun, Andi Batari Annisa; Habbe, Abdul Hamid; Nagu, Nadhirah (Jurnal Multidisiplin Madani, 2024)
This research examines market efficiency in emerging markets through a systematic literature review. Market efficiency, in the context of finance theory, is a condition in which asset prices fully reflect all available information. In emerging markets, achieving efficiency is often constrained by a number of factors. This research finds that emerging markets are generally only able to achieve weak-form efficiency, where prices reflect historical information but fail to fully reflect public or private information quickly and accurately. Limitations in transparency, weak regulation, and insider trading practices hinder the achievement of semi-strong and strong form efficiency. In addition, market anomalies such as price deviations from fundamental values are often found, caused by unstable and asymmetric information distribution